The Omnichannel: Throughout business strategy in an increasingly connected world (Research, Society and Development, 2022)
This scientific work aims at the importance of an analysis of an omnichannel strategy in the times of information and connectivity boom, with the aim of discussing consumer changes in this period. The scenario and how the strategy affects retail companies and the national economy. Emphasizes the importance of digital integration and online channels for the survival of retailers An increasingly competitive market. A bibliographic study was carried out, taking into account contributions from authors such as Kotler and Armstrong, Kotler, Kartajaya, Setiawan, Muller. An analysis of how the retail company Magazine Luiza leverages sales with online and omnichannel strategy stands out, and how it can be the biggest leader in the area in 2020, differentiating itself from competitors, but currently facing challenges and economic instability. The conclusion is the extreme importance for companies to invest in the digital environment, in new online channels and continue to grow and meet customer needs. Finally, this transformation also generates a reflection of the political positioning of a brand in a heterogeneous society.